2021
DOI: 10.1016/j.jse.2020.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Trends in reimbursement for primary and revision total elbow arthroplasty

Abstract: Background: Relative value units (RVUs) are an essential component of reimbursement calculations from the Centers for Medicare & Medicaid Services. RVUs are calculated based on physician work, practice expense, and professional liability insurance. Procedures that are more complex, such as revision arthroplasty, require greater levels of physician work and should therefore be assigned a greater RVU. The purpose of this study is to compare RVUs assigned for primary and revision total elbow arthroplasty (TEA). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The more complicated revision surgery is valued no more than the simpler index operation. 20 This exemplifies another critique of the current RVU system, which is its failure to address the learning curve. As physicians perform more of a procedure and technology improves, the operative time usually goes down.…”
Section: Discussionmentioning
confidence: 99%
“…The more complicated revision surgery is valued no more than the simpler index operation. 20 This exemplifies another critique of the current RVU system, which is its failure to address the learning curve. As physicians perform more of a procedure and technology improves, the operative time usually goes down.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that larger cohort evaluations or the inclusion of revisions may demonstrate longer procedural times, as reported in other studies. 29 Generally, within an academic medical center, attending surgeons are tasked with the responsibility of balancing resident education and providing safe care to patients. These conflicts are additionally complicated by external pressures from health care systems, patients, and family members.…”
Section: Discussionmentioning
confidence: 99%
“…An increased productivity with limiting hospital costs is a driving force in many orthopaedic surgery procedures including TEA. 29 These pressures, coupled with patient and family members becoming increasingly more aware of trainee participation, make training the next generation of surgeons difficult. The findings in the present study are reassuring that trainee participation does not appear to be compromising efficiency for attendings during elbow replacement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies in the field of orthopaedic surgery have suggested that the current RVU system fails to adequately consider the perioperative work and complexity related to various surgical procedures. [5][6][7][8][9] For example, revision surgeries are reimbursed less than their primary counterpart across subspecialties despite the added complexities that are associated with revision procedures. These findings raise concern that inadequate reimbursement may limit access to orthopaedic care among medically complex patients.…”
mentioning
confidence: 99%